The Role of Metalanguage in Supporting Academic Language Development. (13th February 2013) - Schleppegrell, Mary J.
Abstract : Recent currents in language learning research highlight the social and emergent aspects of second language (L2) development and recognize that learners need opportunities for interaction in meaningful contexts supported by explicit attention to language itself. These perspectives suggest new ways of conceptualizing the challenges faced by children learning L2s as they learn school subjects. This article reports on design‐based research in U.S. schools with a majority of English language learners, where teachers were supported in using Systemic Functional Linguistics metalanguage in the context of curricular activities. This work illustrates how a meaningful metalanguage can support L2 learners in accomplishing challenging tasks in the primary school curriculum at the same time that it promotes the kind of focused consciousness‐raising and explicit talk about language that has been shown to facilitate L2 development. Examples from classroom research exemplify how metalanguage supports the situated and contextual language learning that current research in education and L2 acquisition calls for, while also supporting disciplinary goals and activities in English language arts.